"Love is a microbe too"1Letter from Vincent van Gogh to Wilhelmina van Gogh, Arles, between April 28 and May 2, 1889 [original in French], in: van Gogh (2009), letter 764, translated by the author.: Microbiome dialectics. Issue 1 (March 2022) - Zwart, Hub
Abstract: Whereas the Human Genome Project was an anthropocentric research endeavour, microbiome research entails a much more interactive and symbiotic view of human existence, seeing human beings as holobionts, a term coined by Lynn Margulis to emphasise the interconnectedness and multiplicity of organisms. In this paper, building on previous authors, a dialectical perspective on microbiome research will be adopted, striving to supersede the ontological divide between self and other, humans and microbes, and to incorporate the microbiome as a crucial dimension of human existence, not only corporally, but also in terms of mood and cognition. On the practical level, microbiome insights promise to offer opportunities for self-care and self-management, allowing us to consciously interact with our microbiome to foster wellness and health. How to distinguish realistic scenarios from hype? Here again, an interactive (dialectical) approach is adopted, arguing that practices of the self should result from mutual learning between laboratory research and life-world experience.